Livestock depredation and community responses in Bhimsen rural municipality, Gorkha district, Nepal - Patel, Chandesh Prasad; Kafle, Gandhiv (Journal of Agriculture and Natural Resources, 2025)
Conflict between humans and wildlife is a major problem for global wildlife conservation. Conflicts between humans and leopards are common throughout their global range. In Bhimsen Rural Municipality, Gorkha district, Nepal, this study was conducted during 2020-2021 to evaluate livestock depredation by common leopards (Panthera pardus), its causes, and locally implemented mitigation measures. A questionnaire survey was used to triangulate the data from livestock owners' compensation claims submitted to the Division Forest Office (DFO) Gorkha and the Manaslu Conservation Area Office, Manaslu Gorkha (n=113). Goats accounted for the majority of the 91 animals that were killed (mean = 82.5, 91%), followed by cattle (mean = 5, 5.5%) and buffaloes (mean = 3, 3.3%). With the highest monthly losses in December (mean = 15.0) and January (mean = 13.5), depredation peaked in the afternoon (12–5 PM, 33.9%) and late at night (12–5 AM, 20.15%). The conversion of crop land into forest (24.8%), an increase in leopard populations (22.1%), and a decrease in wild prey (20.4%) were the primary apparent causes of the majority of the incidents (58%), which happened within 100 meters of forest edges. Predator-proof corrals (23%) and active guarding (19.5%) were local mitigation measures. The distance from the forest and the incidence of cattle depredation were inversely correlated. The respondents' attitudes toward leopard conservation were favorable. Based on these results, the study suggests improving local conflict-resolution skills and bolstering livestock protection close to forests.